Analysis on the DOA estimation of uniform circular arrays based on compressive sensing - Lin-shu HUANG; Hao CHA; Hui-juan YE; Kai XU (Tongxin xuebao)
In order to alleviate the serious problem of the low angle resolution after miniaturizing the antenna array of the surface wave radar,the compressed sensing method is proposed for radar antenna array angle estimation method.The sparse signals model is established,the application conditions are analyzed,and the measurement matrix is designed based on the real-time sea state information.By using the matching algorithm,the signal reconstruction is carried on.Simulation results show that if it satisfies the reconstruction condition,the azimuth resolution is improved by the method in the cost of the calculating resources.